Северное обнаружение, переописание и галопатия Apocyclops dengizicus (Copepoda, Cyclopoida) - Монченко, В.И. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Полное иллюстрированное переописание вида Аpocyclops dengizicus (Lepeschkin) представлено на материале с северного предела его ареала оз. Сиваш (Гнилое море) и северного побережья Каспийского моря. Впервые детально описаны ротовые конечности с особеностями орнамента, указаны своеобразные вторичнополовые признаки, представлено распространение вида во всемирном масштабе. На северном Каспии вид выявлен при общей солености 1,5‰–5,39‰ и температуре 17–24°С. The redescription of Аpocyclops dengizicus (Lepeschkin) is given based on the specimens from northern boundary of its area — salt lake Sivash (between Kherson and Krimea regions) in Ukraine and northern shore of Caspian Sea in Russia. The oral appendages with their fine structure (ornament) are described in detales, the secondary sexual features are shown, the notes on species world distribution are given. In the north of Caspian Sea this species is recorded at the salinity 1.5‰–5.39‰ and temperature 17–24°С.